Strength and conditioning practices of Brazilian Olympic sprint and jump coaches - Loturco, I.; Haugen, T.; Freitas, T. T.; Bishop, C.; Moura, T. B. M. A.; Mercer, V. P.; Weldon, A.; Alcaraz, P. E.; Pereira, L. A. (Journal of Human Kinetics, 2023)
Olympic coaches are likely to have adequate knowledge and implement effective training programs. This study aimed to describe and critically examine the strength and conditioning practices adopted by Brazilian Olympic sprint and jump coaches. Nineteen Olympic coaches (age: 50.2 ± 10.8 years; professional experience: 25.9 ± 13.1 years) completed a survey consisting of eight sections: 1) background information; 2) strength-power development; 3) speed training; 4) plyometrics; 5) flexibility training; 6) physical testing; 7) technology use; and 8) programming. It was noticed that coaches prioritized the development of explosiveness, power, and sprinting speed in their training programs, given the specific requirements of sprint and jump events. Nevertheless, unexpectedly, we observed: (1) large variations in the number of repetitions performed per set during resistance training in the off-season period, (2) a higher volume of resistance training prescribed during the competitive period (compared to other sports), and (3) infrequent use of traditional periodization models. These findings are probably related to the complex characteristics of modern competitive sports (e.g., congested competitive schedule) and the individual needs of sprinters and jumpers. Identification of training practices commonly used by leading track and field coaches may help practitioners and sport scientists create more effective research projects and training programs.